2012
DOI: 10.1016/j.hrtlng.2012.04.009
|View full text |Cite
|
Sign up to set email alerts
|

What keeps nurses from the sexual counseling of patients with heart failure?

Abstract: OBJECTIVES: We sought to examine the current practice of discussing sexual health by heart failure (HF) nurses, and to explore which barriers prevent nurses from discussing sexuality. less thanbrgreater than less thanbrgreater thanMETHODS: The Nurses Survey of Sexual Counseling of Myocardial Infarction Patients and a list of barriers were used to form a questionnaire, which was sent to all HF clinics (n = 122) in the Netherlands. less thanbrgreater than less thanbrgreater thanRESULTS: The majority (75%) of nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 21 publications
4
66
0
5
Order By: Relevance
“…This low number is in strong contrast with the fact that more than half of the professionals believed that addressing sexuality was a part of their professional responsibilities. Even though this study is, to our knowledge, the first to investigate the sexuality related communication of professionals working with patients with an ULD, other studies focusing on different chronic diseases and/or disabilities have found the same contrast [23][24][25]. This duality can be explained by several reasons.…”
Section: Discussionmentioning
confidence: 63%
“…This low number is in strong contrast with the fact that more than half of the professionals believed that addressing sexuality was a part of their professional responsibilities. Even though this study is, to our knowledge, the first to investigate the sexuality related communication of professionals working with patients with an ULD, other studies focusing on different chronic diseases and/or disabilities have found the same contrast [23][24][25]. This duality can be explained by several reasons.…”
Section: Discussionmentioning
confidence: 63%
“…Doherty and colleges stated that cardiac nurses ignore sexual health assessment because health institutions lack guidelines regarding sexual assessment and management, specialized referral clinics and nurses do not have enough confidence, knowledge and training [34]. Hoekstra et al [5] reported that lack of health policies about addressing sexual health was the main barrier. Furthermore, Quinn and colleagues found that healthcare organization view sexual health assessment is not a priority [33].…”
Section: Organizational-related Barriersmentioning
confidence: 99%
“…Sexual dysfunction is a broad term that reflects any problem which interferes with persons' sexual desire [4]. Sexual dysfunction includes erectile dysfunction, loss of sexual desire, orgasmic difficulties, lack of interest in sex, and feeling afraid by patients or by the partner in having sex [5].…”
mentioning
confidence: 99%
“…Cultural and language barriers may also inhibit sensitive discussions. 15,17,22,[32][33][34][35][36][37][38][39] Although healthcare professionals indicate some knowledge about sexual activity in cardiac populations and are willing to engage in sexual counseling, 22 evidence suggests limited follow-through in providing such interventions to patients 40,41 because of lack of confidence and specialized training, 15,32,42 as well as perceived restrictions in the practice setting 43 and cultural background of the healthcare provider. 33 Specific areas of knowledge to be addressed in staff training are the role of intimacy without sex to gain confidence, positions for sexual activity, use of foreplay before sexual activity, and avoidance of unfamiliar partners and surroundings, 17,36,44 as well as knowledge regarding the use of medications to enhance sexual performance and whether or not these are safe for patients to use with specific types of CVD.…”
mentioning
confidence: 99%